DIGITAL MARKETING FOR YOUTH: OPPORTUNITIES AND PROSPECTS OF FREELANCING PLATFORMS (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article analyzes the role of freelancing activities among youth in ensuring their employment and contributing to the country’s economic growth. Freelancing provides young people with opportunities to achieve financial independence, develop digital skills, and gain international experience. Additionally, the article highlights how freelancing reduces unemployment, facilitates the transition to an innovative economy, and positively impacts the national economy, supported by examples and statistical data. It emphasizes that youth engagement in freelancing not only fosters their personal development but also significantly contributes to the economic stability of the country.